2018
DOI: 10.3390/ijms19082308
|View full text |Cite
|
Sign up to set email alerts
|

Sargassum serratifolium Extract Attenuates Interleukin-1β-Induced Oxidative Stress and Inflammatory Response in Chondrocytes by Suppressing the Activation of NF-κB, p38 MAPK, and PI3K/Akt

Abstract: Osteoarthritis (OA) is a degenerative joint disease that is characterized by irreversible articular cartilage destruction by inflammatory reaction. Among inflammatory stimuli, interleukin-1β (IL-1β) is known to play a crucial role in OA pathogenesis by stimulating several mediators that contribute to cartilage degradation. Recently, the marine brown alga Sargassum serratifolium has been reported to exhibit antioxidant and anti-inflammatory effects in microglial and human umbilical vein endothelial cell models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 36 publications
(44 reference statements)
1
38
0
Order By: Relevance
“…The activated complex can recruit intracellular adaptor proteins and kinases, including MyD88, IRAK4, and IRAK1, and consequently activates downstream kinases IKK-α and IKK-β, which phosphorylate IκB proteins and lead to activation of NF-κB. Although various plant extracts have been reported to inhibit NF-κB activation by suppressing cell inflammatory responses (15), it remains unclear how they suppress NF-κB activation. The present study showed that ginsenoside Rd decreased IL1RAP protein level but not the mRNA level in NP chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The activated complex can recruit intracellular adaptor proteins and kinases, including MyD88, IRAK4, and IRAK1, and consequently activates downstream kinases IKK-α and IKK-β, which phosphorylate IκB proteins and lead to activation of NF-κB. Although various plant extracts have been reported to inhibit NF-κB activation by suppressing cell inflammatory responses (15), it remains unclear how they suppress NF-κB activation. The present study showed that ginsenoside Rd decreased IL1RAP protein level but not the mRNA level in NP chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there are few publications that evaluated COX-2 inhibition by macroalgae lipid extracts, and the ones published used cell lines assays, but not in vitro COX-2 assays. Previous studies evaluated the COX-2 expression, evidencing a reduction of the enzyme expression in cell lines [ 72 , 73 , 74 , 75 ], but polar lipid extracts from terrestrial plants and microalgae showed modulation capacity of COX-2 using in vitro assays [ 75 , 76 ]. The ethanolic extract of the small herbaceous plant Polygonum minus (Huds) achieved 25% of COX-2 inhibition at concentration of 100 μg/mL [ 76 ] which is in the same order of magnitude we obtained in the present study (about 80% inhibition at a concentration of 500 μg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these various biological activities, prenylated xanthones have not been studied for OA. Previous studies have shown that hypoxia or inflammatory induction of SW1353 chondrocytes stimulated by IL-1β, monosodium iodoacetate (MIA), and H 2 O 2 is known as a representative in vitro model for OA studies [ 20 , 21 , 22 , 23 ]. In this study, we investigated the role of prenylated xanthones, cudratricusxanthone O (CTO), isolated from M. tricuspidata , on the suppression of H 2 O 2 -induced cell damage by promoting the Nrf2/HO-1 pathway in SW1353 cells.…”
Section: Introductionmentioning
confidence: 99%